Lifecycle and ecomonical study of selected thermal solar installations - Košičan Jaroslav; Pardo Miguel Ángel; Vilčeková Silvia (Selected Scientific Papers: Journal of Civil Engineering, 2020)
Creating a scheme of solar thermal installations is a mighty move forward to develop a suitable energy standards of residential buildings. In recent years were done many studies, which did a several energy simulations for residence buildings. If design of thermal installation is false, it can lead to rise in the expensive overall energy costs and unsatisfactory thermal comfort in the building. Nowdays, in Slovakia using solar thermal installations are increasing more than in recent years. This research investigates twelve modern solar water heating systems, formed on the roof of the family house. We tried to make analysis, where designed solar energy systems were appropriate and fulfill energy requirements of DHW and heating. The study deals with the best financial alternative of the prepared installations of the house. According to overall prices of installation, energy production of additional source for heating and total system efficiency and lifespan, we found out the best possible choice. Expected amount of the various energy contribution is simulated in specialized program. If we talk about midterm energy values, we can see the best possible choice for the alternatives. In this case we made analysis of these schemes for typical family house in Kosice. We set the limits of the building and analyzed which scheme is the best for need of the yearly average water consumption and heating.